Optimization and Validation of RP-HPLC-UV/VIS Method for Determination Some Antioxidants in Dry Calyces of Iraqi Hibiscus Sabdraffia Linn (Baghdad Science Journal, 2018)
A new (Reversed Phase- High Performance Liquid chromatography) RP-HPLC method with Ultraviolet-Visible spectrophotometry has been optimized and validated for the simultaneous extraction and determination of antioxidants present in Iraqi calyces of Hibiscus Sabdraffia Linn. The method is based on using ultrasonic bath for extracting antioxidants. Limit of detection in μg/ml of Vitamin C, Sabdaretine, Gossypetine, Hibiscetine, Anthocyanins, Dephinidin-3-glucoside were113.8294×10-6,123.0453×10-6,70.3681×10-6,59.6730×10-6,148.1710×10-6,and125.3481×10-6 respectively. The concentration of antioxidants found in dry spacemen of calyces of Iraqi Hibiscus Sabdraffia Linn. under study: Vitamin C, Sabdaretine, Gossypetine, Hibiscetine, Anthocyanins, and Dephinidin-3-glucoside are 258.3 μg/g, 225.51 μg/g, 154.975 μg/g, 111.407 μg/g, 439.442 μg/g, and 185.729 μg/g respectively.